2019
DOI: 10.3892/ijo.2019.4767
|View full text |Cite
|
Sign up to set email alerts
|

C‑mannosylation of R‑spondin2 activates Wnt/β‑catenin signaling and migration activity in human tumor cells

Abstract: , one of the four members of the R-spondin family of proteins, has agonistic activity in the Wnt/β-catenin signaling pathway, and it is associated with normal development, as well as disease, such as cancer. The present study focused on the C-mannosylation of Rspo2, which is a novel and unique type of glycosylation that occurs via a C-C linkage between the tryptophan residue and an α-mannose. Although Rspo2 has two putative C-mannosylation sites at residues Trp 150 and Trp 153 , it had not been reported to dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…There are four homologs of DPY19 (DPY19L1-L4) in mammals, and it has been demonstrated that DPY19L1 and DPY19L3 have a C -mannosyltransferase activity [ 11 , 12 ]. It has been revealed that C -mannosylation involves protein secretion, intracellular localization, and protein folding, which are similar with other forms of glycosylation [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]; however, the role of C -mannosyltransferases on biological events is still obscured.…”
Section: Introductionmentioning
confidence: 99%
“…There are four homologs of DPY19 (DPY19L1-L4) in mammals, and it has been demonstrated that DPY19L1 and DPY19L3 have a C -mannosyltransferase activity [ 11 , 12 ]. It has been revealed that C -mannosylation involves protein secretion, intracellular localization, and protein folding, which are similar with other forms of glycosylation [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]; however, the role of C -mannosyltransferases on biological events is still obscured.…”
Section: Introductionmentioning
confidence: 99%
“…Secretion of C -mannosylation-defective mutants of R-spondin2 was reduced in human fibrosarcoma HT1080, whereas its secretion was increased in other human tumor cell lines, such as A549, PANC1, and MDA-MB-231 [ 65 ]. Thus, the secretion of R-spondin2 was different among tumor cell lines, indicating that the effect of C -mannosylation on R-spondin2 secretion may differ in a cell type-dependent manner.…”
Section: Biochemical Aspects Of Protein C -Mannosylation and C -Man-trpmentioning
confidence: 99%
“…C -Mannosylation of R-spondin1, 2, and 3 enhanced Wnt/β-catenin activation [ 62 , 63 , 65 ]. C -Mannosylation was also involved in the regulation of JAK-STAT signaling through effects on TPOR [ 72 ] or G-CSFR [ 73 ].…”
Section: Biochemical Aspects Of Protein C -Mannosylation and C -Man-trpmentioning
confidence: 99%
See 1 more Smart Citation
“…In regard to human health and protein C-mannosylation, it was reported that blood CMW is elevated in patients with renal dysfunction, including renal diseases associated with type 2 diabetes (1721). As for cancer biology, it was recently reported that C-mannosylation of R-spondin 2 activates Wnt/β-catenin signaling and migration activity in various human tumor cells (22). This study suggested that C-mannosylation of R-spondin 2 is involved in the promotion of cancer progression.…”
Section: Introductionmentioning
confidence: 99%